SHEAR STRENGHT OF SOIL, BEARING CAPACITY AND FOUNDATION - Taufik Dwi Laksono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2006)
AbstractLoading mechanism continued by a foundation is vertical burden and laboring momen at foundation, is mostly arrested by energy support the (bearing capacity) foundation land; ground of at foundation base, and burden level off most arrested by resistance shift the ( sliding resistance) from foundation base.            Foundation function is to continue the superstructure burden to geology surface without abysmal of the land;ground pressure ability. Hence for desain of peaceful foundation have to consider the security to failure shift the land;ground and energy Capacities support the land;ground to avoid the happening of abundant degradation.            In chosening foundation to be used at one particular work, require to be paid attention to by whether that foundation suited for circumstance in field or not, things required to become the consideration is circumstance of land;ground of foundation and boundaries of effect of structure for (superstrukture) of like condition burden, nature of dynamic of building for and other. Keyword: Foundation, energy support, shift land;ground.